Ethnomathematical Exploration of Islamic Inheritance Law: A Content Analysis of the Faraidh Book by Shaykh Muhammad bin Salih Al-'Uthaymeen - Heru Kurniawan; Rofiq Nurhadi; Prasetyo Budi Darmono; Nila Kurniasih (Universitas Islam Sultan Agung, 2026)
This study aims to explore the ethnomathematical elements in Islamic inheritance law through a content analysis of the Kitab Faraidh (Book of Islamic Inheritance) by Shaykh Muhammad bin Salih Al-'Uthaymeen. This classical text presents a systematic exposition of faraidh law based on the Qur'an, Hadith, and scholarly consensus. Using qualitative content analysis, this research identifies and analyzes the mathematical concepts embedded in inheritance division systems as presented in the text. The findings reveal that faraidh constitutes a sophisticated mathematical system implementing fractions, least common multiples (LCM), ratios, and basic arithmetic operations through four main calculation patterns: fixed shares (ashabul furudh), proportional reduction ('aul), proportional addition (radd), and residual distribution ('asabah). The analysis demonstrates that the mathematical complexity in faraidh is equivalent to middle school mathematics curriculum content. This study recommends the integration of faraidh-based ethnomathematics into mathematics education to create contextual, culturally relevant learning. The results offer practical guidance for developing teaching materials and learning models that utilize Islamic intellectual heritage as a pedagogical resource. Keywords: Ethnomathematics, Islamic Inheritance, Contextual Mathematics Learning